Effects Of Repetitive Uncontrolled Temperature Exposure On The Quality Of Packed Red Blood Cells - Hassan, Noor Hamizah Mohd (2019)
Packed Red Blood Cells (PRBC) must be transfused within 30 minutes upon removal from blood refrigerator and the PRBC should not be hold in the ward where the storage temperature is not controlled. Untransfused blood which returned to the blood bank shall be discarded unless it is kept in an appropriate condition and temperature. Intermittent storage outside allowable temperature range often leads to destruction of the PRBC unit. This was a cross sectional study performed to determine the PRBC warming rates and the quality of PRBC upon repetitive exposure to uncontrolled temperature after 30 minutes and 4 hours. In this study four PRBC units (228 mL ± 37mL) collected from eligible volunteer subjects were equivalently split into two units, producing eight smaller units PRBC (±130mL) which then assigned into two groups; control and experimental group. Eight units of PRBC from both control and experimental group were tested on day 1, day 7, day 14 and day 35 of storage for haemoglobin level, haematocrit, haemolysis rate, potassium, lactate dehydrogenase (LDH), pH and sterility. The PRBC warming rate upon exposure to uncontrolled temperature were monitored and recorded. All PRBCs achieved desired quality requirement from national guideline from day 1 to day 35 for haematocrit, haemolysis rate, and sterility. However, none of the PRBC units met the standard requirement (>45g/unit) for haemoglobin starting day 14 to day 35. No significant changes observed for all PRBC’s quality over repetitive exposure to uncontrolled temperature in 35 days in experimental group (P<0.05). There was also no evidence of bacterial contamination in PRBC at the end of their shelf life.